A handbook to the Palace of Minos at Knossos : with its dependencies - Pendlebury, J. (Cambridge library collection. Archaeology, 2014)
Sir Arthur Evans's excavation at the Cretan site of Knossos from 1900 onwards uncovered a previously unknown civilization. His enthusiastic (though controversial) reconstructions of the site and its fresco decorations made it an attractive destination for travellers and tourists, and Evans thought a simple guidebook for visitors would be desirable alongside his own multi-volume work, The Palace of Minos (also reissued in this series). This was published in 1933 by John Pendlebury (1904–41), a brilliant young archaeologist later killed by German troops during the invasion of Crete in 1941. With a foreword by Evans, the handbook is in two parts: an architectural history of the Palace of Minos, and a guide to the site, with a note of the time needed to explore each building, maps showing the best trail to be followed, plans, and detailed descriptions. The book continues to be of value to both archaeologists and tourists.